WACANA KRITIK SOSIAL DALAM KUMPULAN PUISI LEAK JAGAT KARYA I GUSTI PUTU BAWA SAMAR GANTANG - Sadwika, I Nyoman (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 20 (2013): September 2013, 2013)
This study is critical discourse on “Poetry Leak Jagat” by I Gusti Putu Bawa Samar Gantang, The focus of study is the form, function, and meaning of the discourse of social criticism expressed in the text collection of “Poetry Leak Jagat”. For analysis data, this study used theory semiotic. The semiotic theory is systematically understand of production and interpretation of signs, how it works, its benefits and the situation of the human condition. In this study semiotic theory are used to unravel the social criticism contained in the text collection of poetry Leak Jagat. The method used in this research is descriptive analytic method. Data analysis is the process of the reviewers all data obtained through observation, interviews, recording of documents. Results of the study showed that the construction of discourse shaped the discourse of social criticism and political law-themed, misery, and fraud. Social criticism contained in it functions as a critique of law enforcement, the new order until now, the government and the rulers, and the capitalists in the sense that every occur era of corruption, oppression of human rights, and social conflict and the strengthening of national disintegration.
Keywords: critical discourse, poetry, and semiotic